2015
DOI: 10.4236/ajps.2015.611176
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Dormancy of “Tupy” Blackberry in Subtropical Conditions

Abstract: In subtropical or tropical conditions, the insufficient winter chill accumulation is often a limiting factor to break the dormancy of temperate-climate species such as the blackberry, which requires using products to help break dormancy. This study evaluates the efficacy of compounds in breaking dormancy of blackberry and its consequent influence on phenology and crop yields. The experiment was conducted in São Manuel, State of São Paulo, Brazil, in the 2011/2012 production cycle. The plants used were two-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…By considering FNF doses, a quadratic regression model significantly increased flowering percentage, as the maximum value of the function was of 43.7% open flowers at 2.2% ( Figure 2C Furthermore, different nitrogen forms in FNF can cause respiratory stress in the plant buds (SEGANTINI et al, 2015), which not only induces sprouting of vegetative buds, but also increases flower opening; therefore, a positive effect on plants productive traits.…”
Section: Percentage Of Sprouted Bud Flowering and Fruit Setmentioning
confidence: 92%
See 3 more Smart Citations
“…By considering FNF doses, a quadratic regression model significantly increased flowering percentage, as the maximum value of the function was of 43.7% open flowers at 2.2% ( Figure 2C Furthermore, different nitrogen forms in FNF can cause respiratory stress in the plant buds (SEGANTINI et al, 2015), which not only induces sprouting of vegetative buds, but also increases flower opening; therefore, a positive effect on plants productive traits.…”
Section: Percentage Of Sprouted Bud Flowering and Fruit Setmentioning
confidence: 92%
“…In response to product application to overcome dormancy, the highest fruit number was also verified in 'Roxo de Valinhos' fig tree at 6% garlic extract, as produced more fruits in comparison to the other dosages . In 'Tupy' blackberry, Segantini et al (2015) recommend an estimated dose of 5.4% FNF, since it provided the highest fruit production (521 fruits plant -1 ), but doses higher than that reduced plant production. For 'Imperial Gala' apple, it is recommended to use doses below 7% Erger ® , as fruit reduction can happen above that value (HAWERROTH et al, 2010), besides increasing competition between vegetative and reproductive structures.…”
Section: Fruit Number Production and Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies have identified a commercial product called Erger ® as a less dangerous option to stimulate budburst in temperate fruit species. According to manufacturer's guidelines, this product is an organic nitrogen compound which, when mixed with calcium nitrate (Ca(NO 3 ) 2 ), has budbreaking effects on apples (HAWERROTH et al, 2010b; PETRI et al, 2014 and blackberries (SEGANTINI et al, 2015). Therefore, this product could be an alternative with lower environmental risk for dormancy control in the Campanha Gaúcha region.…”
Section: Introductionmentioning
confidence: 99%